Students’ Perceptions of Baamboozle Gamification in Vocabulary Learning: A Case Study of 5th Grade Students’ of MI Darul Ulum Semarang - Hanum, Luthfia; Senowarsito, Senowarsito; Wahyuni, Sri (Innovative: Journal Of Social Science Research, 2025)
This study was conducted with the aim of exploring the perceptions of 5th grade students of MI Darul Ulum Semarang towards the application of Baamboozle application in English vocabulary learning and its impact on student motivation and engagement during classroom learning. The method in this study used qualitative in which the interview instrument was used as primary and observation and documents were secondary. Interview data was taken from 6 grade 5 students, who were randomly selected to be fair. The results of the interview received a very positive response because the use of baamboozle itself is seen as very positive when applied as a learning tool. They stated that Baamboozle is very fun, interesting and not boring. Children became more active and involved in class activities when learning takes place. Teachers were also seen as playing an important role in introducing and guiding during the implementation of Baamboozle. In conclusion, the implementation of Baamboozle is very effective in learning English vocabulary, as evidenced by students' positive perceptions and active engagement during the learning process.